Sustainable management of elasmobranchs in complex coastal fisheries - Gupta, T (2024)
Global trade and use of plants, animals and fungi forms one of the major drivers of biodiversity loss, but simultaneously support the lives and livelihoods of millions of people. Elasmobranchs (sharks and rays) are ecologically and socio-economically important, yet many species face extinction due to overfishing. In countries of the Global South like India, where there are high human populations and dependence on fisheries, the multi-species fisheries and complex socio-economic contexts create an urgent need for sustainable management of elasmobranch fisheries rather than exclusionary conservation measures. My DPhil aimed to understand how the sustainability of elasmobranch fisheries can be improved in such contexts, for the benefit of both biodiversity and people. I first conducted a scoping literature review of shark and ray research in India, identifying critical research gaps that need to be prioritised, such as the socio-economic dimensions of shark and ray fishing, trade and consumption. I examined fishing and trade motivations across the spectrum of elasmobranch catch, from low-value bycatch (like rhino rays) to high-value target species (like blacktip sharks) at two case study sites; Goa and Kakinada. My research uncovered diverse motivations and values underpinning people’s use of elasmobranchs, including instrumental (economic) benefits, food, culture and tradition, which were enabled by mechanisms such as access to capital, social identity and knowledge. I investigated the ecological sustainability of a small-scale blacktip shark fishery, combining data from multiple sources including knowledge from fishers, and found that harvest rates need to be reduced to at least half for sustainability. Finally, I used participatory methods to explore potential conservation strategies and found that voluntary live release measures may be promising for rhino rays, whereas for blacktip sharks a complete exit from the fishery, through a combination of community-based agreements and state enforcement, may be the only option. My work has led to further research and to the design of live release interventions for rhino rays in Goa, which could serve as a scalable conservation model. My research contributes to developing robust approaches for conservation science and practice in data- and resource-limited contexts, and particularly highlights the importance of diverse knowledge systems, such as Local Ecological Knowledge, in ethical and effective conservation planning. I demonstrate the value of local-scale studies to inform the design of nuanced interventions targeted at contextual drivers. My DPhil hence contributes to a better understanding of marine sustainability to support more effective conservation action across scales, towards delivering on global biodiversity targets.